Single-qubit anisotropy induced by micromagnet in Si-MOS quantum dot - Ning Chu; Xin Zhang; Rong-Long Ma; Zhen-Zhen Kong; Wei-Zhu Liao; Sheng-Kai Zhu; Chu Wang; Ao-Ran Li; Gui-Lei Wang; Gang Cao; Hai-Ou Li; Guo-Ping Guo (Applied Physics Express)
Synthesized spin–orbit coupling (SSOC) is crucial for the operation of spin qubits in silicon quantum dot, as it address the challenge posed by the inherently weak intrinsic spin–orbit coupling in silicon. Here, we investigate the anisotropic properties of single spin qubit in silicon metal-oxide-semiconductor (Si-MOS) quantum dot and provide experimental evidence for the control of SSOC. Additionally, we experimentally demonstrate that tuning the operating point away from the conventional configuration can enhance the quality factor of the spin qubit. These findings lay a foundation for the realization of high-quality tunable spin–orbit qubits.